Предмет: Алгебра,
автор: sashaalexsa
решите уравнение (x-2)(x^2+6x+9)=6(x+3)
Ответы
Автор ответа:
0
(x-2)(x²+6x+9)=6(x+3)
(x-2)(x+3)²-6(x+3)=0
(x+3)((x-2)(x+3)-6)=0
(x+3)(x²+3x-2x-6-6)=0
(x+3)(x²-x-12)=0
x+3=0; x=-3; x²-x-12=0 D=7 x₁=(1+7)/2=4; x₂=(1-7)/2=-3
Ответ: -3 и 4
Похожие вопросы
Предмет: Физика,
автор: racheldrp9r7kf
Предмет: Математика,
автор: WOTNHN54HN204NJ024NJ
Предмет: Русский язык,
автор: kistanovivan68
Предмет: Математика,
автор: ddautova1998
Предмет: Математика,
автор: sashunyaivanko